2000
DOI: 10.1149/1.1393370
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating Copper onto Resistive Barrier Films

Abstract: The relentless miniaturization of integrated circuit (IC) feature sizes has pushed mainstay aluminum alloy interconnects into a regime where electromigration failure and interconnect resistance-capacitance (RC) delays are becoming significant concerns. Primarily for these reasons, as well as potential cost and yield benefits of a copper/damascene process, efforts to develop copper interconnect capability have accelerated dramatically in recent years. Integrated circuits containing copper interconnects are now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 5 publications
0
59
0
Order By: Relevance
“…The similar calculations were performed in the literature also [8,11,12]. From the work done by Takahashi [13], the plating current density (i s ) is a function of the conductivity (k m ) of the sputtered seeding layer and the overpotential (Z), i.e. ri m ¼ Àk m r 2 Z ¼ Àai s ðZÞ;…”
Section: Resultsmentioning
confidence: 84%
“…The similar calculations were performed in the literature also [8,11,12]. From the work done by Takahashi [13], the plating current density (i s ) is a function of the conductivity (k m ) of the sputtered seeding layer and the overpotential (Z), i.e. ri m ¼ Àk m r 2 Z ¼ Àai s ðZÞ;…”
Section: Resultsmentioning
confidence: 84%
“…Litearture reports (Chang, 2001) describe that increase in plating current density increased the surface roughness and reduced the grain size of copper films due to an increase of plating overpotential. Several other researchers have demonstrated that the polarization overpotential increased with increasing the plating current density leading to high copper nucleation rate (Takahashi & Gross, 1999a, 2000Tean et al, 2003;Teh et al, 2001). …”
Section: Effect Of Current Density On Copper Electrodepositionmentioning
confidence: 97%
“…The above process parameters have been optimized after several electroplating trials by varying temperature, current density etc., to achieve a void free copper layer with fine grain size which is a very challenging art [13,14]. Figure 5 shows the average surface roughness of the plated copper after (0.2 µm) process optimization measured using Zeta optical profiler.…”
Section: Information Technology and Nanotechnology (Itnt-2016) 154mentioning
confidence: 99%